2018
DOI: 10.15578/jppi.23.4.2017.275-286
|View full text |Cite
|
Sign up to set email alerts
|

Keterkaitan Kondisi Oseanografi Dengan Perikanan Pelagis Di Perairan Selat Bali

Abstract: Perikanan pelagis di perairan Selat Bali telah diusahakan sejak lama. Data runtut tahun hasil tangkapan yang didaratkan cenderung berfluktuasi. Kajian ini bertujuan untuk mengetahui kondisi spasial dan temporal karakteristik oseanografi, terkait dengan dengan dinamika perikanan pelagis di Selat Bali. Data parameter oseanografi meliputi suhu permukaan laut (SPL) dan klorofill-a (chl-a) yang diperoleh dari citra satelit penginderaan jauh Aqua/Terra MODIS, sedangkan data sumberdaya perikanan pelagis berupa hasil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Principle component analysis result showed correlation among variables (left: plot of factor 1 x 2; midle: plot of factor 1 x 3; plot of factor 2 x 3). Finding of this research unanimous of Suniada & Susilo (2017) showed that SST and chl-a was the most significant variabels affecting sardine CPUE. Sardine abundance should be highly determined by chlorophyll-a as their food source (Gaughan & Mitchell, 1999).…”
Section: The Impact Of Changing Environment On Bali Sardine Productionmentioning
confidence: 70%
See 2 more Smart Citations
“…Principle component analysis result showed correlation among variables (left: plot of factor 1 x 2; midle: plot of factor 1 x 3; plot of factor 2 x 3). Finding of this research unanimous of Suniada & Susilo (2017) showed that SST and chl-a was the most significant variabels affecting sardine CPUE. Sardine abundance should be highly determined by chlorophyll-a as their food source (Gaughan & Mitchell, 1999).…”
Section: The Impact Of Changing Environment On Bali Sardine Productionmentioning
confidence: 70%
“…Dynamic of some environment variables (SST/SSTA, chl-a, salinity, thermocline depth and the number of trip) is simultaneously affecting sardine CPUE. This analysis gives more information on the effect of various oceanographic variables to the seasonal variation of sardine CPUE (Suniada & Susilo, 2017). Regional climate phenomenon like IOD and ENSO generated the dynamic of water temperature and upwelling intensity resulted in the changing environment of sardine The fluctuation of SSTA and CPUE of sardine (Sardinella lemuru) in Bali Strait.…”
Section: The Impact Of Changing Environment On Bali Sardine Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studi karakteristik suhu permukaan laut dan konsentrasi klorofil-a di beberapa wilayah diantaranya di perairan Ireland dan Selat Bali (Casal et al, 2015;Suniada et al, 2015), serta konsentrasi klorofil-a di perairan Mediterranean (Kahru et al, 2014;Lavigne et al, 2015) yang merupakan salah satu indikator penting untuk mendeteksi kesuburan perairan. Ikan yang dominan tertangkap di perairan Selat Bali merupakan ikan-ikan pelagis dengan sumber makanan utamanya adalah plankton, sehingga perubahan konsentrasi klorofil-a merupakan salah satu faktor penyebab perubahan jumlah hasil tangkapan (Suniada K. I. dan Eko Susilo, 2018).…”
Section: Gambar 4 Distribusi Spl Dan Klorofil-a Terhadaphasil Tangkaunclassified
“…Bali Strait is a semi-enclosed sea with shallow bathymetric conditions with potential fishery resources (WPP-RI 573). Bali Strait is connected to the Bali Sea in the north and the Indian Ocean in the south, while the west and east sides are bordered by Java Island and Bali Island [1]. Bali Strait waters are strongly influenced by the Monsoon system.…”
Section: Introductionmentioning
confidence: 99%